2020
DOI: 10.33024/jkm.v6i4.2937
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Hypnobirthing Terhadap Lama Persalinan Kala Ii Pada Ibu Bersalin Primigravida

Abstract: Background: The labor process does not run smoothly if it is not handled properly. Hypnobirthing is an alternative to speed up the labor process. This technique aims to make the mother have a calm spirit with positive energy, which helps relieve pain and anxiety during contractions which have an impact on weakening the uterine contractions and causing the labor process to take a long time. Hypnobirthing can eliminate fear of women during childbirth so that the uterine muscles relax. This will make labor easier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
2
0
2
Order By: Relevance
“…Based on the p-value < 0.05, it was concluded that hypnobirthing and rebozo administration affects the duration of delivery during II. The group given hypnobirthing and rebozo had a faster duration of delivery during II than the group that was only given hypnobirthing.The results of this study support the results of the research of Syswianti et al (2020) and Rini (2010) which show that hypnobirthing affects the faster the duration of delivery during II.…”
Section: Results Description Of Research Datasupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the p-value < 0.05, it was concluded that hypnobirthing and rebozo administration affects the duration of delivery during II. The group given hypnobirthing and rebozo had a faster duration of delivery during II than the group that was only given hypnobirthing.The results of this study support the results of the research of Syswianti et al (2020) and Rini (2010) which show that hypnobirthing affects the faster the duration of delivery during II.…”
Section: Results Description Of Research Datasupporting
confidence: 90%
“…A study on hypnobirthing shows that hypnobirthing has an effect on increasing the frequency of uterine contractions, the duration of contractions, the opening of the cervix, and the decrease in the head of the fetus, so that it will speed up the delivery process (Muhidayati et al, 2018). The effect of hypnobirthing on the duration of delivery during II is proven by the research of Syswianti et al (2020) and (Rini, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hasil penelitian Syswianti et al (2020), menunjukkan terdapat pengaruh hypnobirthing terhadap lama persalinan kala II, rata-rata lama persalinan kala II pada kelompok eksperimen adalah 20,24 menit, dan pada kelompok kontrol adalah 20 -45 menit. Hypnobirthing merupakan salah satu upaya nonfarmakologi untuk mengantisipasi adanya stres, respon nyeri dan kecemasan yang berlebihan pada ibu saat menjalani proses persalinan.…”
Section: B Metode Pelaksanaanunclassified
“…Asuhan berdasarkan Filosofi Hypnobirthing yang diberikan pada kelompok intervensi memperpendek durasi persalinan dan mengurangi biaya persalinan. Hypnobirthing berpengaruh terhadap lama kala II pada ibu primigravida (Syswianti et al, 2020) Asuhan suportif hypnobirthing yang diberikan selama persalinan mempersingkat proses persalinan, mengurangi penggunaan analgesia, anestesi dan oksitosin eksternal, dan menurunkan tingkat intervensi persalinan pervaginam dan persalinan SC (AWHONN, 2011) (Hodnett et al, 2013).…”
Section: Pengaruh Hypnobirthing Terhadap Durasi Persalinanunclassified